Industrial Minerals 2005 – Ball Clay - R. L. Virta (Society for Mining, Metallurgy & Exploration, 2006)
Four companies mined ball clay in four states during 2005. They included H.C. Spinks Clay (owned by Franklin Minerals), Kentucky-Tennessee Clay (owned by Imerys), Old Hickory Clay and Unimin. Production was estimated to be 1.32 Mt (1.45 million st) valued at $53.3 million, based on the results of a preliminary survey of the ball clay industry. Production in 2004 was 1.22 Mt (1.34 million st) valued at $54.1 million. Tennessee was the leading ball clay producer state with 61 percent of domestic production, followed by Texas, Mississippi and Kentucky.